A lower bound on the maximum mass if the secondary in GW190814 was once a rapidly spinning neutron star. (24th September 2020) - Most, Elias R; Papenfort, L Jens; Weih, Lukas R; Rezzolla, Luciano
ABSTRACT: The recent detection of GW190814 featured the merger of a binary with a primary having a mass of $\sim 23\, M_{\odot }$ and a secondary with a mass of $\sim 2.6\, M_{\odot }$ . While the primary was most likely a black hole, the secondary could be interpreted as either the lightest black hole or the most massive neutron star ever observed, but also as the indication of a novel class of exotic compact objects. We here argue that although the secondary in GW190814 is most likely a black hole at merger, it needs not be an ab-initio black hole nor an exotic object. Rather, based on our current understanding of the nuclear-matter equation of state, it can be a rapidly rotating neutron star that collapsed to a rotating black hole at some point before merger. Using universal relations connecting the masses and spins of uniformly rotating neutron stars, we estimate the spin, $0.49_{-0.05}^{+0.08} \lesssim χ \lesssim 0.68_{-0.05}^{+0.11}$, of the secondary – a quantity not constrained so far by the detection – and a novel strict lower bound on the maximum mass, $M_{_{TOV}}\gt 2.08^{+0.04}_{-0.04}\, \, M_{\odot }$ and an optimal bound of $M_{_{TOV}}\gt 2.15^{+0.04}_{-0.04}\, \, M_{\odot }$, of non-rotating neutron stars, consistent with recent observations of a very massive pulsar. The new lower bound also remains valid even in the less likely scenario in which the secondary neutron star never collapsed to a black hole.